2006
DOI: 10.1111/j.1440-169x.2006.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal epimorphin is important for pancreatic duct morphogenesis

Abstract: Epithelial-mesenchymal interactions are crucial for the proper development of many organs, including the pancreas. Within the pancreas, the ducts are thought to harbor stem/progenitor cells, and possibly to give rise to pancreatic ductal carcinoma. Little is known about the mechanism of formation of pancreatic ducts in the embryo. Pancreatic mesenchyme contains numerous soluble factors which help to sustain the growth and differentiation of exocrine and endocrine structures. Here, we report that one such morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…More recent studies that aimed to define epithelial lineage-specific responses to mesenchymal signals demonstrated that removal of the pancreatic mesenchyme disrupted acinar cell morphogenesis, thus inhibiting epithelial branching and outgrowth (Gittes et al 1996;Miralles et al 1998). These results clearly defined the dependence of pancreatic epithelial cell fate decisions on mesenchymal cues, and subsequent work has demonstrated that FGF (Bhushan et al 2001), EGF (Tulachan et al 2006), retinoic acid (Stafford et al 2006), WNT (Jonckheere et al 2008), and bone morphogenetic protein (Ahnfelt-Rønne et al 2010) are important mediators of this process. Similar to pancreatic epithelial cell development during organogenesis, the paracrine signaling networks between the pancreatic epithelium and its adjacent stroma in cancer development have been the subject of intense scrutiny.…”
mentioning
confidence: 77%
“…More recent studies that aimed to define epithelial lineage-specific responses to mesenchymal signals demonstrated that removal of the pancreatic mesenchyme disrupted acinar cell morphogenesis, thus inhibiting epithelial branching and outgrowth (Gittes et al 1996;Miralles et al 1998). These results clearly defined the dependence of pancreatic epithelial cell fate decisions on mesenchymal cues, and subsequent work has demonstrated that FGF (Bhushan et al 2001), EGF (Tulachan et al 2006), retinoic acid (Stafford et al 2006), WNT (Jonckheere et al 2008), and bone morphogenetic protein (Ahnfelt-Rønne et al 2010) are important mediators of this process. Similar to pancreatic epithelial cell development during organogenesis, the paracrine signaling networks between the pancreatic epithelium and its adjacent stroma in cancer development have been the subject of intense scrutiny.…”
mentioning
confidence: 77%
“…One question is which factor in Matrigel leads to spheroid formation, since Matrigel contains various growth factors and ECM [32]. Matrigel has been reported to contain epimorphin [47] and an epimorphin-neutralizing antibody blocks development of the cystic ductal structures cultured on Matrigel [48]. It remains a possibility that proteases derived from Matrigel but not from hepatocytes contribute to spheroid formation, because Matrigel has been reported to contain inactive proteases [49].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, 9- cis retinoic acid (9cRA) inhibits acinar differentiation in the developing pancreas, in favor of ducts, and 9cRA does not induce ductal differentiation in the absence of mesenchyme or following inhibition of laminin signaling [69]. Another mesenchyme-derived soluble factor selectively promoting pancreatic ductal proliferation and differentiation is epimorphin (syntaxin 2), which is also known to induce epithelial branching in a variety of tissues [71, 72]. …”
Section: Regulation Of Exocrine Differentiation By Soluble Morphogensmentioning
confidence: 99%